THE CONCEPT OF MODERN ECOLOGY IN THE FOCUS OF SOCIAL-PHILOSOPHICAL AND SCIENTIFIC KNOWLEDGE - Shorina, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Despite precautions of the world community against global social and environmental problems, the scientists of the Club of Rome still testify the crisis of the world’s development. The aim and tasks. The aim is to find out the potential of the philosophical worldview in the complex of scientific and ecological knowledge and the place of the concept of "sustainable development" in solving the problems of the environmental crisis as a modern global "challenge". One of the tasks is to clarify the modern understanding of the term "ecology" and its subject range. Research methods. The theory and method of discourse analysis, the method of comparative analysis, as well as system-logical, dialectic, analytical, synthetic and structural research methods are applied. Research results. Today classical ecology or ecology as a biological discipline is only a natural component of modern ecology. The modern understanding of ecology gives a generalized understanding of the interaction between man and nature, the biosphere and the technosphere, nature, culture, and civilization as a whole. Therefore, its subject goes beyond the boundaries of biological science. Modern ecological knowledge becomes the knowledge of human ecology, such a study that combines the achievements of science and philosophy of nature, in particular the philosophy of ecology. Discussion. An important philosophical and methodological approach to the analysis of an environmental problem is to identify its connection with various aspects of social life and its social and moral assessment. It is considered to bewrong to believe that the environment, human nature, science, and technology caused the problem by themselves. The reasons lie in the market nature of the development of material productive forces and private goals of social production, which limit the possibilities of rational and comprehensive use of the forces and resources of nature to meet the needs of the crisis-free technical and social progress. Conclusion The concept of sustainable development is a modern attempt to provide a theoretical and practical solution to the global problems of our time. The reduction of anthropogenic influence on biosphere, ensuring its healthy reproduction should be associated with a change of the market value system and behaviour stereotypes (greed, short-sightedness, and impatience) of the modern Western civilization.